Pengaruh Terapi Komplementer Akupresur terhadap Mual Muntah Pasca Operasi di RSUD Dr. H. Abdul Moeloek Provinsi Lampung - El Rahmayati; Anggi Irawan; Tumiur Sormin (Politeknik Kesehatan Tanjung Karang, 2017)
Postoperative Nausea and vomiting (PONV) is a common complication after surgery.The incidence of postoperative nausea vomiting is approximately 30% of all patients undergoing inpatient surgery and 70% of cases occur within the first 24 hours. One of nausea and vomiting treatment is non-pharmacological therapies with complementary acupressure therapy. Furthermore, the research was conducted to determine the effect of acupressure complementary therapies against postoperative nausea and vomiting.The research was Quasi-Experimental research design Non-equivalent Control Group, the sampling technique used purposive sampling technique. Based on results of sample calculation used amounted to 22 respondents, consisting of 11 experimental groups and 11 control groups. Collecting data was used questionnaire and analyzed using univariate and bivariate analysis by Wilcoxon and Mann-Whitney with α values (<0.05).The results showed the difference in score of nausea and vomiting the first and second measurements in the control group given a placebo action is 0.91 with a p-value (0.26). Nausea and vomiting difference in scores obtained before and after acupressure complementary therapies in the experimental group was 2:18 with a p-value (0.004). As well as the difference in scores obtained post-operative nausea and vomiting in the control group and the experiment is 1:27 with the p-value (0.009). The above statistical test results can be concluded that there was the effect of complementary acupressure therapy on postoperative nausea vomiting. Based on the conclusion of the research, the authors suggest that complementary acupressure therapy can be applied as a companion therapy and it is expected that nursing staff can learn complementary acupressure therapy.